2016
DOI: 10.1038/celldisc.2016.15
|View full text |Cite
|
Sign up to set email alerts
|

Osteoclast-derived microRNA-containing exosomes selectively inhibit osteoblast activity

Abstract: MicroRNAs have an important role in bone homeostasis. However, the detailed mechanism of microRNA-mediated intercellular communication between bone cells remains elusive. Here, we report that osteoclasts secrete microRNA-enriched exosomes, by which miR-214 is transferred into osteoblasts to inhibit their function. In a coculture system, inhibition of exosome formation and secretion prevented miR-214 transportation. Exosomes specifically recognized osteoblasts through the interaction between ephrinA2 and EphA2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
261
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 265 publications
(273 citation statements)
references
References 68 publications
11
261
0
1
Order By: Relevance
“…In another aspect, osteoclasts could also secret exosomes to modulate osteoblast function. Sun et al provided evidences and testified that osteoclasts secreted circulating miR-214 to inhibit osteoblast activity[18]. In agreement with the above findings, we showed that osteoblasts harbored high level of miR-433-3p (Fig 3) which might secret to circulating or tissue space.…”
Section: Discussionsupporting
confidence: 90%
“…In another aspect, osteoclasts could also secret exosomes to modulate osteoblast function. Sun et al provided evidences and testified that osteoclasts secreted circulating miR-214 to inhibit osteoblast activity[18]. In agreement with the above findings, we showed that osteoblasts harbored high level of miR-433-3p (Fig 3) which might secret to circulating or tissue space.…”
Section: Discussionsupporting
confidence: 90%
“…Finally, they showed that the inhibition of osteoclastic-specific miR-214-3P enhanced bone formation in aging OVX mice. A recent study also showed that osteoclasts produced miRNA-enriched exosomes, and the exosomes transferred miR-214 into the osteoblasts to inhibit their activity (Sun et al, 2016). Osteoblast activity was inhibited in osteoclast-specific miR-214 transgenic mice.…”
Section: The Role Of Osteoclast In Bone Formationmentioning
confidence: 99%
“…110 These antagomirs could also attenuate bone loss in aged OVX mice as well. A particularly exciting finding from this work, and another recent study 111 was that osteoclast-derived exosomes enriched in miR-214 could apparently be transferred to osteoblasts to inhibit bone formation. This data proposes the existence of miRNA-mediated cross-talk between osteoclasts and osteoblasts via exosomes to control bone homeostasis.…”
Section: Other Functional Mirnas With Therapeutic Potential To Treat mentioning
confidence: 59%